Dynamics of the use of magnetocardiography in the study of the cardiac conduction system of the chick embryo. Issue 20 (13th August 2020) - Schellpfeffer, Michael A.; Strasburger, Janette F.; Baffa, Oswaldo; Strand, Sarah A; Lutter, William; Phan, Tan; Wakai, Ronald T.
Abstract: Introduction: Human fetal magnetocardiography (fMCG) has been done for several decades to evaluate fetal arrhythmias using a superconducting quantum interference device (SQUID) magnetometer, but there is little work in embryonic/fetal animal models. This study uses an optically‐pumped magnetometer (OPM) to obtain an fMCG in the chick embryo. Methods: White Leghorn chick embryos were examined from incubation Day #10–19. Different examination chambers were tested to optimize embryonic thermal stability and magnetic signal acquisition. All examinations were done with magnetic shielding. The OPM sensors were placed next to the egg shell. The embryo's position was localized by transilluminating the intact egg or ultrasound imaging the egg with an open air cell to optimize sensor placement. The raw data for each embryo was postprocessed to obtain a fMCG composite waveform. Results: fMCG's were obtained in embryos from Day #12 to 19. The best success with intact eggs was obtained using five sensors; one at the bottom and four around the lower perimeter of the egg at 90° intervals with the egg oriented vertically and the air cell up. Using ultrasound imaging with the air cell open only two sensors were necessary, one at the bottom and one laterally next to the embryo. fMCGs were analyzed for heart rate and rhythm, each portion of the PQRST waveform, and the PR interval, QRS complex, RR interval, and QT interval. Conclusions: This study validates the chick embryo as an animal model to study in a longitudinal and noninvasive fashion the fetal cardiac conduction system by using OPM magnetocardiography.